The impact of agricultural subsidies on farm production: A synthetic control method approach - Matej Opatrny (Charles University in Prague, Institute of Economic Studies (IES), 2018)
Czech farmers experienced an enormous exogenous shock when they joined the common agricultural market (CAM) and the Common Agricultural Policy (CAP) in 2004. Using the World Bank's dataset, we apply the synthetic control method to establish a counterfactual case of the Czech Republic food production index in the absence of the CAM and CAP. The results show that the Czech Republic would have had a higher food index if it had not entered the CAM and CAP. Moreover, we show that the CAP and CAM had different impacts on farms in the Czech Republic and Bulgaria, which have the most comparable agriculture according to the results of the synthetic control method.
Keywords: C10; Q10; Q18; 330; Common Agriculture Policy; Common Agricultural Market; Subsidies; Farms; Synthetic Control Method